A Closed Lateral Subtalar Dislocation With Checkrein Deformity of Great Toe due to Entrapment of Flexor Hallucis Longus: A Case Report. Issue 5 (October 2016) - Tanwar, Yashwant Singh; Singh, Satyaprakash; Arya, Rajender Kumar; Aujla, Navneet; Mathur, Ashish; Kharbanda, Yatinder
Closed lateral subtalar dislocation is a very rare injury. We report a case of closed lateral subtalar dislocation with entrapment of flexor hallucis longus tendon producing a checkrein deformity. The patient was managed immediately with closed reduction under regional anesthesia and fixated with percutaneous Kirschner wires. Early mobilization and weightbearing was started and there were no complications till the last follow-up visit. Levels of Evidence: Therapeutic, Level IV: Case study